Celovit geriatrični pregled - nov sistematični pristop v obravnavanju geriatričnih bolnikov - Šabovič, Mišo (Medicinski razgledi, 2004)
In the article the comprehensive geriatric assessment (CGA) - a new systematicapproach to the collection of patient data that allows appropriate evaluation of chronic diseases, gerontologic syndromes and functional impairment, is presented. According to CGA, first subjective and objective database is collected, then integrated into an assessment (particular attention is focused on the nine main problem issues), and finally a care planis created in cooperation with a patient and relatives. CGA was developed in USA and has been shown useful in the clinical practice. In the clinical trials it has been revealed that use of CGA improves the quality of life of geriatric patients and probably prolongs the life. It is realistic that the implication of CGA would result in improved medical care of old people in our specific local conditions as well.
Keywords: Anamneza; Geriatric Assessment; Fizikalna preiskava; Medical History Taking; Physical Examination; Geriatrična ocena; Starostniki; Aged; geriatrija; zdravniški pregledi; storostniki